INFLUENCE OF NEGATIVE INTEREST RATES ON ENDOWEMENTS AND FOUNDATIONS FUNCTIONING - Nikolić, Dušan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Negative interest rate exists in the case when on the basis of the deposit contract a deponent is obliged to pay to a depository (a bank) a reimbursement for the money keeping (paying to save). The scientific literature indicates that the legal regulation on endowments and foundations in a vast number of countries is based on the presumption that interest rates cannot be negative and that we are encountering the phenomenon of which we have limited knowledge. The introduction of negative interest rates, thus, could endanger the functioning, if not the subsistence of some endowments and foundations. The vulnerable social groups could, thereby, be especially affected. The Law on Endowments and Foundations of the Republic of Serbia enshrines that the endowments' capital shall not fall under the minimum capital assets of 30.000 EUR recalculated in dinars based on the middle exchange rate of the National Bank of Serbia on the day of establishment. Apart from that, a founder may in the Articles of Association determine the minimum value below which the capital assets of endowment may not be reduced, which may not be lower of the minimum assets value set by the Law. In Serbia negative interest rates could aggravate, and throughout the time, even prevent the accomplishment of aims of endowments and foundations which for the operation of their activities may use only the interest yields and not the means of capital assets above the legal minimum. Some endowments could even cease to exist due to the diminishment of their minimum capital assets which entirely consist of the money deposited in the banks. The Article indicates the need for reconsidering the legal norms currently in force and that the transformation of certain legal institutes shall timely commence, whereby their systematic and social functions shall be regarded, as well as the need for introducing a streamlined corrective mechanisms with the aim of protecting interests of the weaker party in civil law relations.